A dynamic timeslot-based multicast bandwidth advance reservation algorithm for enterprise video conferencing systems - Zhiwen LIAO; Ling ZHANG (Dianxin kexue)
In order to guarantee the service quality of video conferencing and improve the utilization of enterprise network resources, the problem of bandwidth advance reservation for enterprise video conferencing system was studied. In an enterprise network, there could be hundreds of conferences held at the same time, and video communication was possible between any two participants. Reserving bandwidth resources in advance for a conference would result in fine-grained changes in available bandwidth over time. In particular, when a large number of conference requests occur at the same time, time consumption and bandwidth usage would increase significantly. To address this problem, a dynamic timeslot-based multicast bandwidth advance reservation algorithm was proposed. The algorithm also took into account the two conference scenarios proposed by the IETF XCON working group. The simulation results show that compared with other algorithms, the algorithm can effectively reserve bandwidth for big data conferences and solve the problem of time overhead bottleneck.